Needs Analysis and Design of Problem-Based Learning E-Book on Solid Geometry Material - Syaila Musyafirah; Usman Mulbar (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
Abstrack Mathematics learning, particularly on solid geometry, still faces challenges in students’ conceptual understanding and engagement due to the dominance of conventional teaching approaches. This study aims to analyze the needs and design an e-book based on Problem Based Learning (PBL) as an alternative innovative teaching material. The method used is library research by reviewing relevant literature on mathematics education, PBL, and digital learning media. The e-book design refers to the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation, with this study focusing on the analysis and design stages. The results indicate that the e-book is systematically designed by integrating PBL, starting from problem orientation, investigation, to evaluation, and is supported by multimedia elements such as images, animations, and videos. This integration produces a contextual, interactive design that supports independent learning. Therefore, the contextually designed PBL-based e-book has the potential to serve as an effective learning medium to enhance students’ conceptual understanding and promote more active, interactive, and independent learning processes.